WP1-18 Risk factors and patterns of recurrence of low grade glioma: a systematic review. Issue 3 (14th February 2019) - Narbad, V; Lavrador, JP; Elhag, A; Acharya, S; Hanrahan, J; Vergani, F; Bhangoo, R; Ashkan, K
Abstract : Objectives: To review the risk factors and patterns of progression/recurrence of low grade glioma (LGG). Design: Systematic review of the published literature. Subjects: Inclusion criteria were peer reviewed publications of cohort studies of recurrent/progressive LGG. Studies of wider populations were included if relevant LGG data could be analysed separately. Methods: Medline and Cochrane databases were searched using MeSH and non-MeSH terms, including 'glioma', 'astrocytoma', 'oligoastrocytoma', 'diffuse glioma', 'oligodendroglioma', 'low grade' and 'disease recurrence' by two independent reviewers. Results: Overall, 917 studies were screened, of which 57 studies met the inclusion criteria. The most frequently described risk factor for recurrent LGG was suboptimal extent of resection (EOR) of the initial tumour (in 20 studies); recurrence was also associated with the patient's age (2), tumour location (4), neurological status (3), tumour volume (6), bihemispherical tumour (3) and astrocytic histology (6). IDH mutation was associated with recurrence in 1 out of 3 studies, but TP53 mutation (2 of 4) and MGMT methylation status (4) were not. Malignant transformation was associated with TP53 mutations (3), IDH mutation (1) and EOR (1). Favourable progression free survival (PFS) and/or overall survival (OS) were associated with greater EOR (16), oligodendroglioma histology (2 of 4), initial KPS (3) and the use of adjuvant therapies (9 of 14). IDH mutation was associated with improved PFS and OS (3 of 4). TP53 mutation improved PFS in 1 of 3 studies. MGMT methylation and 1 p/19q codeletion may predict treatment response but their effects on survival are unclear. Conclusions: Astrocytoma histology, IDH and TP53 mutation statuses and surgical treatment (EOR) are essential in determining the time to recurrence or progression in LGG.